2022
DOI: 10.1007/s10479-021-04511-4
|View full text |Cite
|
Sign up to set email alerts
|

Dependence structure between Indian financial market and energy commodities: a cross-quantilogram based evidence

Abstract: Given the developing nations are moving towards attaining the sustainable energy future, the reliance on renewable energy solutions is rising. Therefore, the dependence on traditional fossil fuel-based solutions is getting reduced, and this might have an impact on the energy market commodities. Analyzing this impact might divulge several insights regarding the portfolio decisions, in presence of the transformations in developmental trajectory. In this study, we analyze the cross-quantile dependence of the retu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Since then, this concept has been called green supplier selection, and many researchers developed it over time (Liang et al 2020a , b ). As mentioned above, the selection of green suppliers explores the supplier’s environmental impact, and by reducing destructive effects (Sinha et al 2022 ), it enhances recycling capabilities, prevents wastewater and reduces air emissions, and contributes to improving the life worth (Khokhar et al 2020a , b ). In consideration of government pressure and competition, the choice of green suppliers has shifted from the selection of SS to social and economic performance (Khan et al 2020 ).…”
Section: Theoretical Background On Supplier Selection (Ss)mentioning
confidence: 99%
“…Since then, this concept has been called green supplier selection, and many researchers developed it over time (Liang et al 2020a , b ). As mentioned above, the selection of green suppliers explores the supplier’s environmental impact, and by reducing destructive effects (Sinha et al 2022 ), it enhances recycling capabilities, prevents wastewater and reduces air emissions, and contributes to improving the life worth (Khokhar et al 2020a , b ). In consideration of government pressure and competition, the choice of green suppliers has shifted from the selection of SS to social and economic performance (Khan et al 2020 ).…”
Section: Theoretical Background On Supplier Selection (Ss)mentioning
confidence: 99%
“…The aftereffects of the uneven effect of oil cost changes on the financial development and the economic expansion in middle east emerging countries and in third world countries couldn't reject in this point of view (Du et al, 2010;Farzanegan and Markwardt, 2009). Recent evidence suggested that oil prices rise effects just about all market producing channels; the accumulated evidence approved the great connection between the cost of oil and macroeconomic movement since the oil emergency of the 1970 s (Anuar et al, 2021;Sinha et al, 2022;Żywiołek et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The variables used for the energy commodity prices include Brent, Global Energy Commodity (GEnergy), Heating Oil (HOil), Natural Gas (Ngas), and Petroleum (Pet) futures markets. Due to their large market capitalization and important role in portfolio diversification with other financial assets, these commodities were chosen (Rehman and Vo, 2021;Dmytrów et al, 2021;Sinha et al, 2022).…”
Section: Data Sources and Descriptionmentioning
confidence: 99%